The role of framing, inequity and history in a corruption game: Some experimental evidence - Ananish Chaudhuri; Tirnud Paichayontvijit; Erwann Sbai (Games, 2016)
We investigate the role of framing, inequity in initial endowments and history in shaping behavior in a corrupt transaction by extending the one-shot bribery game introduced by Cameron et al. (2009) to a repeated game setting. We find that the use of loaded language significantly reduces the incidence of bribery and increases the level of punishment. Punishment of bribery leads to reduced bribery in future. The evidence suggests that this game captures essential features of a corrupt transaction, over and above any sentiments of inequity aversion or negative reciprocity However, showing subjects the history of past play has little effect on the level of corruption.
Keywords: C91; D73; O17; K42; 330; corruption; experiments; bribes; punishment; framing